Reexamining Student-Athlete GPA - James E. Johnson; Roger D. Wessel; David Pierce (University of Kansas Libraries, 2010)
A sample of 674 first-year student-athletes at a midsize Midwestern university were examined each year over a five-year period (2004-2008) to determine if athletic variables were powerful enough to be used in conjunction with traditional predictors of college success to predict GPA. The four specific athletic variables unique to student-athletes (i.e., sport, coaching change, playing time, team winning percentage), were hypothesized to be as predictive as traditional variables. Pearson correlations revealed student-athletes were more likely to earn a high first-year GPA if they were female (r = .35), Caucasian (r = -.33), scored well on standardized tests (r = -.47), had a respectable high school GPA (r = .64), were ranked high in their graduating high school class (r = -.58), had a relatively large high school graduating class (r = .15) were not undecided about major (r = -.11), were not a member of a revenue sport (r = .33), and earned a considerable amount of playing time in their first year (r = -.15). Least squares linear regression demonstrated the traditional variables of gender (B = .16), race (B = -.26), standardized test scores (B = .03), high school GPA (B = .41), high school rank (B < -.01), and size of high school graduating class (B < .01) were most influential in predicting first-year student-athlete GPA.